Pengaruh Earning Per Share dan Dividen Per Share Terhadap Harga Saham - Provita Nur Abdillah; Heikal Muhammad Zakaria (Jurnal Dinamika Ekonomi & Bisnis, 2021)
The purpose of this research is to find out the effect of EPS and DPS on the share price of Bank Badan Usaha Milik Negara (BUMN) Banks from 2012 to 2019 obtained from the websites of each bank. The method applied is multiple linear regression analysis with the SPSS version 21. This research shows that EPS has a simultaneous effect on stock prices with a significance of 0.03 < 0.05, then the first hypothesis is accepted. DPS has no partial effect on stock prices with a significance of 0.647 > 0.05, so the second hypothesis is rejected. Then simultaneously, EPS and DPS have an effect on stock prices with a significance value of 0.009 < 0.05, the third hypothesis is accepted. The coefficient of determination test results show that the share price is influenced by the variable EPS and DPS of 23.7%, the rest is influenced by other ratios that have not been examined in this study of 76.3%.